Flame-retardant real silk fiber material, flame-retardant real silk fabric and preparation method of flame-retardant real silk fiber material
Through the modification of silk fibers or fabrics, the silk fabrics are solved by using hydroxylated modified lignin sulfonate and metal salts, as well as a combination of chitosan, citric acid and tannin, combined with heat treatment and water washing. The hidden dangers of burning houses during combustion have achieved efficient improvement of flame retardant performance and maintenance of breathable performance.
Patent Information
- Application Number
- CN202411449885.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Silk fabrics have major fire and safety risks when burning, and the prior art is difficult to improve their flame retardant performance while maintaining their excellent comfortable and breathable properties.
By modifying silk fibers or fabrics in a mixed solution of hydroxylated modified lignin sulfonate and metal salts, and in a mixed solution of chitosan, citric acid and tannin, combined with heat treatment and water washing treatment , improve its flame retardant performance while maintaining breathable performance.
It significantly improves the flame retardant performance of silk fibers and fabrics, and maintains excellent flame retardant performance after multiple washes. It has strong water-resistant performance and basically does not affect breathable performance.
Smart Images

Figure CN119162825A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of textile materials, and in particular to a flame-retardant silk fiber material and a flame-retardant silk fabric and a preparation method thereof. Background Art
[0002] Silk fabric has excellent comfort, breathability and skin-friendliness, and is widely used in clothing and decorative furniture. Its skin-friendliness is unmatched by any other fabric. However, curtains, wall coverings, home clothes, carpets and fabric sofas in residents' lives and their combustion, the fact also shows that clothing and decorative furniture in residents' lives cause a large proportion of fire and safety hazards. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a flame retardant silk fiber material and a flame retardant silk fabric and a preparation method thereof.
[0004] To achieve the above object, the technical solution adopted by the present invention is: a flame retardant silk fiber material, wherein the silk fiber is modified by the following steps in sequence to obtain the flame retardant silk fiber material; (1) immersing the silk fiber in a mixed solution of hydroxylated modified lignin sulfonate and a metal salt at 70-85° C. for 45-75 minutes, wherein the metal salt is calcium chloride, magnesium chloride or aluminum chloride; (2) controlling the milling rate of the silk fiber treated in step (1) to be 75% to 100%, and immersing the silk fiber in a mixed solution of chitosan, citric acid and tannic acid at 70 to 85° C. for 45 to 75 minutes; (3) baking the silk fiber treated in step (2) at 120-150° C. after controlling the rolling rate to be 90%-120%; (4) After baking, rinse with water and let dry naturally.
[0005] The flame retardant silk fiber material is modified in a mixed solution of hydroxylated modified lignin sulfonate and metal salt, and modified in a mixed solution of chitosan, citric acid and tannic acid in turn, thereby improving the flame retardant properties of the silk fiber material without affecting the air permeability of the silk fiber material. The modification in a mixed solution of hydroxylated modified lignin sulfonate and metal salt, and the modification in a mixed solution of chitosan, citric acid and tannic acid are combined, and the silk material still maintains excellent flame retardant properties and strong water washing resistance after multiple water washings.
[0006] Preferably, the concentration of the hydroxylated modified lignin sulfonate is 50-80 g / L, and the hydroxylated modified lignin sulfonate is hydroxylated modified sodium lignin sulfonate.
[0007] The hydroxylated modified sodium lignin sulfonate is used in the modification of the flame retardant silk fiber material, and the concentration of the hydroxylated modified sodium lignin sulfonate is controlled, so that the flame retardant property of the flame retardant silk fiber material is better.
[0008] Preferably, the preparation method of the hydroxylated modified lignin sulfonate is: (a) mixing a mixed aqueous solution of lignin sulfonate and hydrogen peroxide with ferric hydroxide and reacting the mixture in a water bath at 70-90° C. for 30-60 minutes; the weight ratio of lignin sulfonate: hydrogen peroxide: ferric hydroxide is 10: (3-5): (1.5-3); (b) After separating and removing the iron hydroxide in the mixed solution, the pH is adjusted to below 6.5 and the solid is collected as hydroxylated modified lignin sulfonate.
[0009] Preferably, in step (1), the concentration of the metal salt is 1.5-3 g / L.
[0010] Preferably, in step (2), the concentration of chitosan is 18-25 g / L, the weight ratio of chitosan to tannic acid is 10:(0.5-1.5), and the weight ratio of chitosan to citric acid is 10:(0.5-1).
[0011] The combination of the chitosan, tannic acid and citric acid makes the modified flame-retardant silk fiber material have better flame-retardant properties and better water-washing resistance.
[0012] Preferably, in step (3), the baking time is 1 to 2.5 hours.
[0013] Preferably, the silk fiber is mulberry silk, tussah silk, castor silk or cassava silk.
[0014] The present invention also provides a flame-retardant silk fabric, which is woven from any of the flame-retardant silk fiber materials mentioned above.
[0015] The present invention also provides a flame retardant silk fabric, which is obtained by subjecting the silk fabric to modification treatments in the following steps in sequence: (1) immersing the silk fabric in a mixed solution of hydroxylated modified lignin sulfonate and a metal salt at 70-85° C. for 45-75 minutes, wherein the metal salt is calcium chloride, magnesium chloride or aluminum chloride; (2) the silk fabric treated in step (1) is immersed in a mixed solution of chitosan, citric acid and tannic acid at 70 to 85° C. and kept warm for 45 to 75 minutes after the residual rate is controlled to be 75% to 100%. (3) baking the silk fabric treated in step (2) at 120-150° C. after controlling the residual rate to be 90%-120%; (4) After baking, rinse with water and let dry naturally.
[0016] The flame retardant silk fabric is modified in a mixed solution of hydroxylated modified lignin sulfonate and metal salt, and modified in a mixed solution of chitosan, citric acid and tannic acid in turn, thereby improving the flame retardant properties of the flame retardant silk fabric without affecting the breathability of the flame retardant silk fabric. The above-mentioned modification in a mixed solution of hydroxylated modified lignin sulfonate and metal salt, and the modification in a mixed solution of chitosan, citric acid and tannic acid are combined, and the flame retardant silk fabric still maintains excellent flame retardant properties after multiple washings, and has strong water washing resistance.
[0017] Preferably, in step (1), the concentration of the hydroxylated modified lignin sulfonate is 50-80 g / L, and the hydroxylated modified lignin sulfonate is hydroxylated modified sodium lignin sulfonate.
[0018] Preferably, the preparation method of the hydroxylated modified lignin sulfonate is as follows: (a) mixing lignin sulfonate with a mixed aqueous solution of hydrogen peroxide and ferric hydroxide and reacting them in a water bath at 70-90° C. for 30-60 minutes; the weight ratio of lignin sulfonate: hydrogen peroxide: ferric hydroxide is 10: (3-5): (1.5-3); (b) separating and removing the ferric hydroxide in the mixed solution, adjusting the pH to below 6.5, and collecting the solid as the hydroxylated modified lignin sulfonate.
[0019] Preferably, the concentration of the metal salt is 1.5-3 g / L.
[0020] Preferably, in step (2), the concentration of chitosan is 18-25 g / L; the weight ratio of chitosan to tannic acid is 10:(0.5-1.5), and the weight ratio of chitosan to citric acid is 10:(0.5-1).
[0021] Preferably, in step (3), the baking time is 1 to 2.5 hours.
[0022] Preferably, the silk fabric is a textile fabric of mulberry silk, tussah silk, castor silk or cassava silk.
[0023] The present invention provides a method for preparing a flame retardant silk fabric, the method comprising the following steps: (1) immersing the silk fabric in a mixed solution of hydroxylated modified lignin sulfonate and a metal salt at 70-85° C. for 45-75 minutes, wherein the metal salt is calcium chloride, magnesium chloride or aluminum chloride; (2) the silk fabric treated in step (1) is immersed in a mixed solution of chitosan, citric acid and tannic acid at 70 to 85° C. and kept warm for 45 to 75 minutes after the residual rate is controlled to be 75% to 100%. (3) baking the silk fabric treated in step (2) at 120-150° C. after controlling the residual rate to be 90%-120%; (4) After baking, rinse with water and let dry naturally.
[0024] Preferably, in step (1), the concentration of the hydroxylated modified lignin sulfonate is 50-80 g / L, and the hydroxylated modified lignin sulfonate is hydroxylated modified sodium lignin sulfonate.
[0025] Preferably, the preparation method of the hydroxylated modified lignin sulfonate is as follows: (a) mixing lignin sulfonate with a mixed aqueous solution of hydrogen peroxide and ferric hydroxide and reacting them in a water bath at 70-90° C. for 30-60 minutes; the weight ratio of lignin sulfonate: hydrogen peroxide: ferric hydroxide is 10: (3-5): (1.5-3); (b) separating and removing the ferric hydroxide in the mixed solution, adjusting the pH to below 6.5, and collecting the solid as the hydroxylated modified lignin sulfonate.
[0026] Preferably, the concentration of the metal salt is 1.5-3 g / L.
[0027] Preferably, in step (2), the concentration of chitosan is 18-25 g / L; the weight ratio of chitosan to tannic acid is 10:(0.5-1.5), and the weight ratio of chitosan to citric acid is 10:(0.5-1).
[0028] Preferably, in step (3), the baking time is 1 to 2.5 hours.
[0029] Preferably, the silk fabric is a textile fabric of mulberry silk, tussah silk, castor silk or cassava silk.
[0030] The beneficial effects of the present invention are as follows: the present invention provides a flame-retardant silk fiber material and a flame-retardant silk fabric and a preparation method thereof; the flame-retardant silk fiber material and the flame-retardant silk fabric of the present invention are sequentially modified in a mixed solution of hydroxylated modified lignin sulfonate and a metal salt, and modified in a mixed solution of chitosan, citric acid and tannic acid, thereby improving the flame retardant properties of the flame-retardant silk fabric, and does not affect the air permeability of the flame-retardant silk fabric; the above-mentioned modification in a mixed solution of hydroxylated modified lignin sulfonate and a metal salt, and the modification in a mixed solution of chitosan, citric acid and tannic acid are combined, and the flame-retardant silk fabric still maintains excellent flame retardant properties after being washed multiple times, and has strong water washing resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a flame retardant performance test result diagram of the flame retardant silk fabric of an embodiment of the present invention after being washed. DETAILED DESCRIPTION
[0032] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0033] Example 1 As a flame retardant silk fiber material in an embodiment of the present invention, the silk fiber is subjected to the following modification treatments in sequence to obtain the flame retardant silk fiber material; (1) immersing the silk fiber in a mixed solution of hydroxylated modified lignin sulfonate and metal salt at 70-85° C. for 45-75 minutes, wherein the metal salt is calcium chloride, magnesium chloride or aluminum chloride, the concentration of the metal salt is 1.5-3 g / L, and the silk fiber is mulberry silk, tussah silk, castor silk or cassava silk; (2) Controlling the milling rate of the silk fiber treated in step (1) to 75% to 100%, immersing the silk fiber in a mixed solution of chitosan, citric acid and tannic acid at 70 to 85° C. for 45 to 75 minutes; the concentration of the chitosan is 18 to 25 g / L, the weight ratio of the chitosan to the tannic acid is 10:(0.5 to 1.5), and the weight ratio of the chitosan to the citric acid is 10:(0.5 to 1); (3) baking the silk fiber treated in step (2) at 120-150° C. after controlling the rolling rate to 90%-120% for 1-2.5 hours; (4) After baking, rinse with water and let dry naturally.
[0034] Wherein, the concentration of the hydroxylated modified lignin sulfonate is 50-80 g / L, the hydroxylated modified lignin sulfonate is hydroxylated modified sodium lignin sulfonate, and the preparation method of the hydroxylated modified lignin sulfonate is: (a) mixing a mixed aqueous solution of lignin sulfonate and hydrogen peroxide with ferric hydroxide and reacting the mixture in a water bath at 70-90° C. for 30-60 minutes; the weight ratio of lignin sulfonate: hydrogen peroxide: ferric hydroxide is 10: (3-5): (1.5-3); (b) After separating and removing the iron hydroxide in the mixed solution, the pH is adjusted to below 6.5 and the solid is collected as hydroxylated modified lignin sulfonate.
[0035] Example 2 As a flame retardant silk fabric in the embodiment of the present invention, the silk fabric is modified by the following steps in sequence to obtain the flame retardant silk fabric. The silk fabric selected in this embodiment is silk double crepe, 52g / m 2 ; (1) immersing the silk fabric in a mixed solution of 60 g / L hydroxylated modified sodium lignin sulfonate and a metal salt, heating the solution to 80° C. and keeping the solution warm for 60 minutes. The metal salt is calcium chloride, and the concentration of calcium chloride is 2 g / L. (2) the silk fabric treated in step (1) was controlled to have a residual rate of 85% and then immersed in a mixed solution of chitosan, citric acid and tannic acid, and the temperature was raised to 80° C. and kept warm for 60 minutes; the concentration of chitosan was 20 g / L; the weight ratio of chitosan to citric acid was 10:1, and the weight ratio of chitosan to tannic acid was 10:0.8; (3) the silk fabric treated in step (2) is baked at 130° C. for 1.5 hours after the residual rate is controlled to be 105%; (4) After baking, rinse with deionized water and allow to dry naturally.
[0036] The preparation method of the hydroxylated modified sodium lignin sulfonate is as follows: (a) mixing sodium lignin sulfonate with a mixed aqueous solution of hydrogen peroxide and ferric hydroxide and reacting in a water bath at 80°C for 45 minutes; the weight ratio of lignin sulfonate: hydrogen peroxide: ferric hydroxide is 10:4:2; the concentration of sodium lignin sulfonate is 50 g / L; (b) separating and removing the ferric hydroxide in the mixed solution, adjusting the pH to below 6.5, and collecting the solid as hydroxylated modified sodium lignin sulfonate.
[0037] Example 3 As a flame-retardant silk fabric according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 2 is that magnesium chloride is used instead of calcium chloride.
[0038] Example 4 As a flame retardant silk fabric of an embodiment of the present invention, the only difference between this embodiment and embodiment 2 is that in step (2), the silk fabric treated in step (1) is immersed in a mixed solution of chitosan, citric acid and tannic acid, heated to 80°C and kept warm for 60 minutes after the residual rate is controlled to be 75%.
[0039] Example 5 As a flame retardant silk fabric of an embodiment of the present invention, the only difference between this embodiment and embodiment 2 is that in step (2), the silk fabric treated in step (1) is immersed in a mixed solution of chitosan, citric acid and tannic acid and heated to 80° C. for 60 minutes after the residual rate is controlled to be 95%.
[0040] Example 6 As a flame retardant silk fabric according to an embodiment of the present invention, the only difference between this embodiment and embodiment 2 is that the silk fabric treated in step (1) is immersed in a mixed solution of chitosan, citric acid and tannic acid and heated to 70° C. for 60 minutes after the residual rate is controlled to be 85%.
[0041] Example 7 As a flame-retardant silk fabric according to an embodiment of the present invention, the only difference between this embodiment and embodiment 2 is that in step (1), the concentration of the hydroxylated modified sodium lignin sulfonate is 50 g / L.
[0042] Example 8 As a flame-retardant silk fabric according to an embodiment of the present invention, the only difference between this embodiment and embodiment 2 is that in step (1), the concentration of hydroxylated modified sodium lignin sulfonate is 70 g / L.
[0043] Example 9 As a flame-retardant silk fabric according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 2 is that in the step (1), the concentration of the hydroxylated modified sodium lignin sulfonate is 80 g / L.
[0044] Comparative Example 1 As a flame retardant silk fabric of the comparative example of the present invention, the only difference between this comparative example and Example 2 is that in the step (1), no calcium chloride is added, that is, the silk fabric is immersed in a 60 g / L solution of hydroxylated modified sodium lignin sulfonate and the temperature is raised to 80° C. and kept warm for 60 minutes.
[0045] Comparative Example 2 As a flame-retardant silk fabric of the comparative example of the present invention, the only difference between this comparative example and Example 2 is that in the step (1), sodium lignin sulfonate is used to replace the hydroxylated modified sodium lignin sulfonate.
[0046] Comparative Example 3 As a flame retardant silk fabric of the comparative example of the present invention, the only difference between this comparative example and Example 2 is that in step (2), the concentration of chitosan is 5 g / L, the concentration of tannic acid is 2 g / L, and the concentration of citric acid is 1.6 g / L.
[0047] Comparative Example 4 As a flame retardant silk fabric of the comparative example of the present invention, the only difference between this comparative example and Example 2 is that in step (2), tannic acid is not added, that is, the silk fabric treated in step (1) is immersed in a mixed solution of chitosan and citric acid, heated to 80°C and kept warm for 60 minutes after the residual rate is controlled to be 85%.
[0048] Comparative Example 5 As a flame retardant silk fabric of the comparative example of the present invention, the only difference between this comparative example and Example 2 is that in step (2), citric acid is not added, that is, the silk fabric treated in step (1) is immersed in a mixed solution of chitosan and tannic acid, heated to 80°C and kept warm for 60 minutes after the residual rate is controlled to be 85%.
[0049] 1. Experimental Methods 1. 52g / m 2The silk double crepe is cut into 5 cm × 15 cm specifications, and flame retardant silk fabrics are prepared according to Examples 2-9 and Comparative Examples 1-5, with 6 pieces prepared for each example; the solution in step (1) and step (2) is used to immerse the silk double crepe, and the silk fabric is unfolded when immersed. The reference product is 52 g / m 2 Silk crepe de chine.
[0050] 2. Air permeability test: Use YG461E-Ⅱ fully automatic air permeability tester to perform air permeability test under the same parameter conditions as GB / T 5453. Set up 3 samples in parallel.
[0051] 3. Flame retardant performance test.
[0052] The limiting oxygen index (LOI) of silk fabrics was tested on a FTTO 0080 automatic oxygen index instrument in accordance with GB / T 5454 "Textile Combustion Performance Test Oxygen Index Method". Three samples were set in parallel.
[0053] 4. Test of flame retardant properties after washing.
[0054] Bath ratio 1:50, silk and wool detergent 3.7g / L, preheat the vertical decontamination test machine to 40℃, stir at 80 r / min, rinse twice with deionized water after washing, and dry naturally. Test the flame retardant properties using the above flame retardant properties test method.
[0055] The limiting oxygen index of the silk fabric was tested after being washed 1, 2, 3, 4 and 5 times according to the above method.
[0056] 2. Experimental results.
[0057] 1. The test results of air permeability and flame retardancy of Examples 2-9 and Comparative Examples 1-5 are shown in Table 1.
[0058] Table 1 Air permeability and flame retardancy of silk fabrics sample Air permeability (mm / s) Limiting oxygen index (LOI / %) Example 2 504.8 32.4 Example 3 500.3 31.9 Example 4 504.3 30.6 Example 5 500.3 33.0 Example 6 500.8 31.2 Example 7 505.0 31.7 Example 8 506.9 32.8 Example 9 505.9 32.7 Comparative Example 1 505.4 26.7 Comparative Example 2 505.9 29.4 Comparative Example 3 488.4 25.8 Comparative Example 4 492.3 28.6 Comparative Example 5 497.7 29.2 Reference 508.3 24.6 As can be seen from Table 1, the flame retardant silk fabric is modified in a mixed solution of hydroxylated modified lignin sulfonate and metal salt, and modified in a mixed solution of chitosan, citric acid and tannic acid, which improves the flame retardant properties of the flame retardant silk fabric, and basically does not affect the air permeability of the flame retardant silk fabric. The air permeability of Comparative Examples 3, 4 and 5 in the above experimental results is low, indicating that the modification method in the above modification also has an impact on the air permeability. Although the modification of Comparative Examples 3, 4 and 5 can also improve the flame retardant properties to a certain extent, the impact on the air permeability is greater.
[0059] 2. The silk fabrics of Examples 2, 3 and Comparative Examples 1-5 were tested according to the above-mentioned test method for flame retardancy after washing. The experimental results are as follows: Figure 1 shown.
[0060] Depend on Figure 1 It can be seen that after multiple strong washings, the flame retardant properties of the silk fabrics of Examples 2 and 3 remain basically unchanged. On the contrary, after multiple strong washings, the flame retardant properties of the silk fabrics of Comparative Examples 3, 4 and 5 slowly decrease. This shows that the flame retardant silk fabric of the present invention still maintains excellent flame retardant properties and has strong water washing resistance after multiple washings.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A flame retardant silk fiber material, It is characterized in that The silk fiber is modified by the following steps in sequence to obtain a flame retardant silk fiber material; (1) immersing the silk fiber in a mixed solution of hydroxylated modified lignin sulfonate and a metal salt at 70-85° C. for 45-75 minutes, wherein the metal salt is calcium chloride, magnesium chloride or aluminum chloride; (2) controlling the milling rate of the silk fiber treated in step (1) to be 75% to 100%, and immersing the silk fiber in a mixed solution of chitosan, citric acid and tannic acid at 70 to 85° C. for 45 to 75 minutes; (3) baking the silk fiber treated in step (2) at 120-150° C. after controlling the rolling rate to be 90%-120%; (4) After baking, rinse with water and let dry naturally.
2. The flame retardant silk fiber material according to claim 1, It is characterized in that The concentration of the hydroxylated modified lignin sulfonate is 50-80 g / L, the hydroxylated modified lignin sulfonate is hydroxylated modified sodium lignin sulfonate, and the preparation method of the hydroxylated modified lignin sulfonate is: (a) mixing a mixed aqueous solution of lignin sulfonate and hydrogen peroxide with ferric hydroxide and reacting the mixture in a water bath at 70-90° C. for 30-60 minutes; the weight ratio of lignin sulfonate: hydrogen peroxide: ferric hydroxide is 10: (3-5): (1.5-3); (b) After separating and removing the iron hydroxide in the mixed solution, the pH is adjusted to below 6.5 and the solid is collected as hydroxylated modified lignin sulfonate.
3. The flame retardant silk fiber material according to claim 1, It is characterized in that In the step (1), the concentration of the metal salt is 1.5-3 g / L.
4. The flame retardant silk fiber material according to claim 1, It is characterized in that In the step (2), the concentration of chitosan is 18-25 g / L, the weight ratio of chitosan to tannic acid is 10:(0.5-1.5), and the weight ratio of chitosan to citric acid is 10:(0.5-1).
5. The flame retardant silk fiber material according to claim 1, It is characterized in that In the step (3), the baking time is 1 to 2.5 hours, and the silk fiber is mulberry silk, tussah silk, castor silk or cassava silk.
6. A flame retardant silk fabric, It is characterized in that The flame-retardant silk fiber fabric is woven from the flame-retardant silk fiber material as described in any one of claims 1 to 5.
7. A flame retardant silk fabric, It is characterized in that The silk fabric is modified by the following steps in sequence to obtain the flame-retardant silk fabric; (1) immersing the silk fabric in a mixed solution of hydroxylated modified lignin sulfonate and a metal salt at 70-85° C. for 45-75 minutes, wherein the metal salt is calcium chloride, magnesium chloride or aluminum chloride; (2) the silk fabric treated in step (1) is immersed in a mixed solution of chitosan, citric acid and tannic acid at 70 to 85° C. and kept warm for 45 to 75 minutes after the residual rate is controlled to be 75% to 100%. (3) baking the silk fabric treated in step (2) at 120-150° C. after controlling the residual rate to be 90%-120%; (4) After baking, rinse with water and let dry naturally.
8. The flame retardant silk fabric according to claim 7, It is characterized in that In the step (1), the concentration of the hydroxylated modified lignin sulfonate is 50-80 g / L, the hydroxylated modified lignin sulfonate is hydroxylated modified sodium lignin sulfonate, and the preparation method of the hydroxylated modified lignin sulfonate is: (a) mixing the lignin sulfonate with a mixed aqueous solution of hydrogen peroxide and ferric hydroxide and reacting them in a water bath at 70-90° C. for 30-60 minutes; the weight ratio of lignin sulfonate: hydrogen peroxide: ferric hydroxide is 10: (3-5): (1.5-3); (b) separating and removing the ferric hydroxide in the mixed solution, adjusting the pH to below 6.5, and collecting the solid as the hydroxylated modified lignin sulfonate; The concentration of the metal salt is 1.5-3 g / L; In the step (2), the concentration of chitosan is 18-25 g / L; the weight ratio of chitosan to tannic acid is 10:(0.5-1.5), and the weight ratio of chitosan to citric acid is 10:(0.5-1); In the step (3), the baking time is 1 to 2.5 hours, and the silk fabric is a textile fabric made of mulberry silk, tussah silk, castor silk or cassava silk.
9. A method for preparing a flame retardant silk fabric, It is characterized in that The method comprises the following steps: (1) immersing the silk fabric in a mixed solution of hydroxylated modified lignin sulfonate and a metal salt at 70-85° C. for 45-75 minutes, wherein the metal salt is calcium chloride, magnesium chloride or aluminum chloride; (2) the silk fabric treated in step (1) is immersed in a mixed solution of chitosan, citric acid and tannic acid at 70 to 85° C. and kept warm for 45 to 75 minutes after the residual rate is controlled to be 75% to 100%. (3) baking the silk fabric treated in step (2) at 120-150° C. after controlling the residual rate to be 90%-120%; (4) After baking, rinse with water and let dry naturally.
10. The method for preparing the flame-retardant silk fabric according to claim 9, It is characterized in that In the step (1), the concentration of the hydroxylated modified lignin sulfonate is 50-80 g / L, the hydroxylated modified lignin sulfonate is hydroxylated modified sodium lignin sulfonate, and the preparation method of the hydroxylated modified lignin sulfonate is: (a) mixing the lignin sulfonate with a mixed aqueous solution of hydrogen peroxide and ferric hydroxide and reacting them in a water bath at 70-90° C. for 30-60 minutes; the weight ratio of lignin sulfonate: hydrogen peroxide: ferric hydroxide is 10: (3-5): (1.5-3); (b) separating and removing the ferric hydroxide in the mixed solution, adjusting the pH to below 6.5, and collecting the solid as the hydroxylated modified lignin sulfonate; The concentration of the metal salt is 1.5-3 g / L; In the step (2), the concentration of chitosan is 18-25 g / L; the weight ratio of chitosan to tannic acid is 10:(0.5-1.5), and the weight ratio of chitosan to citric acid is 10:(0.5-1); In the step (3), the baking time is 1 to 2.5 hours, and the silk fabric is a textile fabric made of mulberry silk, tussah silk, castor silk or cassava silk.
Citation Information
Patent Citations
Method for preparing environment-friendly flame-retardant silk fabric
CN104611910A
Soluble polyelectrolyte compound and method for flame-retardant finishing of protein fiber
CN109281168A
Anti-flaming silk, preparation method and application thereof
CN109371660A
Flame-retardant silk prepared from flavone and metal salt as well as preparation method and application thereof
CN109457470A
Biomass-based flame-retardant silk fabric and preparation method thereof
CN110130104A
Cited By
Nano real silk fabric material and preparation method thereof
CN120625373A
